Highly suspicious and unfairly cute - Hibbert, Talia (Joy Revolution, 2023)
"Bradley Graeme is pretty much perfect: he's a star football player, manages his OCD well (enough), and comes out on top in all his classes...except the ones he shares with Celine Bangura. They used to be best friends, until Brad decided he was too cool for conspiracy-theory-obsessed Celine and literally abandoned her for the popular kids' table. (At least, that's how Celine sees it.) These days, there's nothing between them but insults and academic rivalry. So when Celine signs up for a two-part survival course in the woods, the last thing she expects is to find Brad right beside her. Forced to work as a team for the chance to win the grand prize, Celine and Bradley must trudge through not just mud and dirt, but their messy past. As this adventure brings them closer together, they start to remember all the good bits of their history. But has too much time passed...or just enough to spark a whole new kind of relationship?"--Dust jacket flap.